A novelty method of multi-scale toughening cement-based materials: Reactive powder concrete with endogenous whiskers. (1st June 2022) - Xu, Xun; Li, Yingjiang; Yu, Bo; Zhu, Bei; Liu, Qian; Hu, Hailong; Hu, Zongyue; Yu, Bowen; Wang, Shuang; Meng, Jie
Abstract: In order to improve the toughness of reactive powder concrete doped steel fibers, a novelty method of multi-scale toughening cement-based materials was investigated. The multi-scale synergistic toughening cement-based materials (nominated basic magnesium sulfate cement-based reactive powder concrete, BMSC based RPC) were designed and discussed for the first time by endogenous whiskers and doped steel fibers. Through orthogonal trials, curing regimes, sand packing and optimization of steel fibers dosage, the synergistic toughening at different microscales was realized by using the properties of endogenous whiskers (the 5·1·7 phase) and doped steel fibers. The results showed that the 28-day flexural strength and compressive strength of BMSC based RPC were 21.4 MPa and 120.5 MPa under ambient temperature curing, respectively, when the steel fibers dosage was 2% (volume fraction). The preliminary research proved that the toughness of reactive powder concrete can be further improved under the multi-scale synergistic toughening effect of endogenous whiskers and doped steel fibers. Highlights: BMSC based RPC was prepared by in-situ growth fibers. The optimum mix proportion and curing regimes of BMSC based RPC was obtained. The 28-day flexural and compressive strength were 21.4 MP and 120.5 MPa.